2016
DOI: 10.1101/mcs.a001339
|View full text |Cite
|
Sign up to set email alerts
|

Progeroid syndrome patients with ZMPSTE24 deficiency could benefit when treated with rapamycin and dimethylsulfoxide

Abstract: Patients with progeroid syndromes such as mandibuloacral dysplasia, type B (MADB) and restrictive dermopathy (RD) harbor mutations in zinc metalloproteinase (ZMPSTE24), an enzyme essential for posttranslational proteolysis of prelamin A to form mature lamin A. Dermal fibroblasts from these patients show increased nuclear dysmorphology and reduced proliferation; however, the efficacy of various pharmacological agents in reversing these cellular phenotypes remains unknown. In this study, fibroblasts from MADB pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 64 publications
1
13
1
Order By: Relevance
“…Rapamycin treatment may be a therapeutic strategy for MADB as well. Indeed, it has been demonstrated that inhibition of the mTOR signaling pathway induces improvement of nuclear aberrations and ameliorates the overall phenotype of fibroblasts from MADB patients, even if changes in the phosphorylation status of mTOR have not been determined ( Figure 4 ) [ 171 ].…”
Section: Progeroid Laminopathiesmentioning
confidence: 99%
“…Rapamycin treatment may be a therapeutic strategy for MADB as well. Indeed, it has been demonstrated that inhibition of the mTOR signaling pathway induces improvement of nuclear aberrations and ameliorates the overall phenotype of fibroblasts from MADB patients, even if changes in the phosphorylation status of mTOR have not been determined ( Figure 4 ) [ 171 ].…”
Section: Progeroid Laminopathiesmentioning
confidence: 99%
“…Additionally, fibroblasts of a patient with ZMPSTE24 deficiency have been recently reported to exhibit improved nuclear morphology and cell proliferation after treatment with rapamycin and dimethylsulfoxide. This observation may open a novel therapeutic avenue for restrictive dermopathy in the future (Akinci et al , 2017).…”
Section: Discussionmentioning
confidence: 88%
“…Previously, a dose of 0.1% DMSO was shown to induce epigenetic modifications, which impaired the expression of genes involved in cellular senescence and DNA repair in a 3D maturing cardiac model [ 3 ]. In contrast, 1% DMSO exposure significantly improved the nuclear morphology and antioxidant status of dermal fibroblasts [ 8 ]. This improvement was determined to be even higher than that observed in known antioxidants, such as N-acetylcysteine [ 8 ] Similarly, in colon cancer cells, low DMSO doses (0.1–1.5%) were shown to reduce the cellular levels of reactive oxygen species (ROS) and the cells proliferative activity relative to the control [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, 1% DMSO exposure significantly improved the nuclear morphology and antioxidant status of dermal fibroblasts [ 8 ]. This improvement was determined to be even higher than that observed in known antioxidants, such as N-acetylcysteine [ 8 ] Similarly, in colon cancer cells, low DMSO doses (0.1–1.5%) were shown to reduce the cellular levels of reactive oxygen species (ROS) and the cells proliferative activity relative to the control [ 9 ]. Literature has further shown that the addition of DMSO (1%) to culture medium at the formation stage of cardiomyocyte progenitor cells stimulates the differentiation of pluripotent stem cells (PSCs) into cardiomyocytes by a 1.5-fold increase [ 10 ].…”
Section: Introductionmentioning
confidence: 99%